Analisis Perencanaan Kapasitas Produksi Menggunakan Metode Rough Cut Capacity Planning (RCCP) untuk Mencapai Target Produksi Benang Plastik Polypropylene (PP) pada Line Lohia 1 - Agustina, Nur Hayati; Purnama, Jaka (Fakultas Teknik UMRI, 2026)
PT XYZ is a manufacturing company that produces Polypropylene (PP) plastic yarn as raw material for woven bags and jumbo bags. The problem on the Lohia 1 Line is that the production target of 17,000 kg/day has not been achieved because the available production capacity does not meet production requirements. This study aims to analyze the suitability between capacity requirements and available production capacity using the Rough Cut Capacity Planning (RCCP) method. The research used data from the 2025-2026 period through demand forecasting, preparation of the Master Production Schedule (MPS), Bill of Resources calculation, and preparation of an RCCP report comparing actual capacity requirements with available capacity. The results show that the available production capacity is unable to meet capacity requirements in all twelve planning periods (under-capacity condition). The highest capacity requirement occurred in September 2026 at 635.33 hours, while the available capacity was only 446.62 hours, resulting in a capacity shortage of 188.71 hours. Capacity adjustment is needed through downtime reduction, improved machine effectiveness, and additional operating hours to support the achievement of production targets.